Nitrogen balance and efficiency as indicators for monitoring the proper use of fertilizers in agricultural and livestock systems - Oliveira, Joyce Graziella; Santana Júnior, Mário Luiz; Maia, Nayane Jaqueline Costa [UNESP]; Dubeux Junior, José Carlos Batista; Gameiro, Augusto Hauber; Kunrath, Taise Robinson; Mendonça, Gabriela Geraldi; Simili, Flávia Fernanda (Springer Nature, 2022)
The rational use of nutrients is a key factor for the sustainability of agricultural systems. This study aimed to analyze the nitrogen balance and use efficiency, and the valorization of organic residues within integrated systems, in comparison to conventional agricultural and livestock systems. The experiment was assembled in a randomized blocks design with three replicates. Six production systems were compared, grain maize production (CROP) and pasture for beef cattle production (LS), and four ICLS (Integrated Crop-Livestock System) for grain maize and pastures for beef cattle, in 2 years. In order to estimate the nutrients balance, inputs, and outputs at farm levels were considered, and with the results obtained for nutrient balance, the use efficiency was calculated. The CROP presented higher nutrient use efficiency (1.43 kg/ha−1), but at the same time, it resulted in negative contributions for the nutrient balance (−97 kg/ha−1) because of lower amounts of nitrogen in the organic residues (188 kg/ha−1) and lower valuation. The LS and ICLS provided a higher amount of nitrogen (983 kg/ha−1; mean ± 921 kg/ha−1) and valuation of organic residues. The presence of components such as pastures and the animal contribute to a positive production system, while reducing the needs for chemical fertilizers.